PELATIHAN MEDIA PEMBELAJARAN PEMBUATAN KTI MENGGUNAKAN MS WORD PADA SISWI SMP IBRAHIMY 3 SUKOREJO - Anisa Anisa; Ismawati Ismawati; Zaehol Fatah (Jurnal Riset Sistem Informasi, 2025)
Scientific writing skills (KTI) and Microsoft Word proficiency are essential for students starting in junior high school. This community service activity aims to improve the student council (OSIS) of Ibrahimy 3 Sukorejo Junior High School's (SMP Ibrahimy 3 Sukorejo) ability to structure scientific papers using Microsoft Word features. The training lasted two hours, from 12:30 to 2:30 p.m. WIB (Western Indonesian Time), using a demonstration approach and hands-on practice. The activity included a needs survey for participants, material preparation, two training sessions (theory and practice), and evaluations based on interactive quizzes and individual practice. The training materials covered the structure of scientific papers and the use of Microsoft Word features, such as headings, margins, page numbering, and an automatic table of contents. Evaluation results showed that 80% of participants were in the "Good" to "Very Good" category, with satisfaction scores ranging from 3.6 to 3.9 on a scale of 4. These findings indicate that the training was well-received and effective in improving participants' academic literacy and digital skills